Strategi Adaptasi Ekonomi Perantau Nias di Kecamatan Tarutung Kabupaten Tapanuli Utara - Danila Mendrofa; Elvri Teresia Simbolon; Yulia Kurnia Sari Sitepu; Harisan Boni Firmando; Masniar Hernawaty Sitorus (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The Nias tribe generally chooses urban areas as a place to migrate because the city symbolizes dynamism and is the center of all progress. People who decide to migrate must determine the right destination area. The people of Nias migrate to an area or leave their area for several reasons. Firstly, economic reasons, the difficulty of meeting living needs in their hometown is one of the factors that most influences the migration activities carried out by the people of Nias. Secondly, there is a social reason, there is an opinion that people who migrate to the other side are considered to have broader experience/insight, have a lot of wealth and money. Third, family reasons, the people of Nias migrate because they already have or have had family members or friends who have migrated first. In this research, researchers focused on the economic adaptation strategies of Nias migrants who migrated to Tarutung sub-district. The researcher chose the title of this research to find out how Nias migrants adapt to the economy in Tarutung. Researchers chose to conduct research on economic adaptation strategies for Nias migrants in Tarutung because the economy is a fundamental aspect of human life, including migrants. The type of research used in this research is qualitative approach research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior.